Punishment controls helper defence against egg predators but not fish predators in cooperatively breeding cichlids - Naef, Jan; Taborsky, Michael (Animal behaviour, 2020)
Helping behaviour in some cooperative breeders is apparently maintained by a combination of coercion and reciprocity. In such pay-to-stay systems, alloparental brood care of subordinate group members functions as a service to dominants, which tolerate subordinates based on how much help they provide. Cooperative territory defence is a key task of cooperative breeders, but it is unknown how territory defence by subordinates is socially regulated. Diverse costs and benefits associated with defending the territory against different threats suggest that these defence behaviours may be maintained through divergent selection regimes, and they might be regulated through different social processes. In the cooperatively breeding cichlid fish Neolamprologus pulcher, unrelated subordinates help defend the territory against egg predators even if they do not participate in reproduction and therefore do not suffer direct or indirect fitness costs through predators of eggs. This behaviour has therefore been interpreted as altruistic service to dominants. Subordinates also defend the group territory against predators of juveniles and adults, which might at least partly reflect their own direct fitness interests and could be maintained through mutualistic interactions among group members. Here, we directly compared the regulation of these two types of defence behaviours and tested whether they are enforced by breeders. We prevented subordinates from defending the territory against egg predators or predators of adults and observed whether they received more aggression in response to this treatment. We found that subordinates received more aggression from breeders after withholding defence against egg predators, but not after withholding defence against fish predators. This suggests that territory defence against egg predators by helpers is enforced by breeders and hence subject to negotiations and trading, whereas defence against fish predators is probably based on mutualistic fitness benefits. •Pay-to-stay negotiations in Neolamprologus pulcher involve commodity-specific punishment.•Cooperative territory defence is mutualistic or enforced depending on intruder type.•Commodity trading in cooperative breeders is tuned to individual fitness interests.